Meningkatkan Kemampuan Membaca dan Kepercayaan Diri Pada Salah Satu Anak Di Panti Asuhan Solaya - Malida Putri; Nicolas Septian Siahaan (Yayasan Literasi Sains Indonesia, 2022)
Reading is something that must be mastered by every human being because reading is a basic science in life. Why should humans be able to read? Because every information such as school lessons, lectures, news that you want to find must be in books and other media, where in the book or media there are lots of readings that contain that information. If not smart or not good at reading then we will have difficulty in obtaining information. This is experienced by a child at the Solaya orphanage where the child is not fluent in reading, this happens because the learning process is not optimal at the school in the area where he used to live, beside that he also looks shy and lacks confidence. Through this field work practice, the practitioner wants to teach the child to read and motivate the chid to be more confident, The practitioner uses the case work stages (Skidmore in Adi, 2013) consisting of the Assesment, Program Planning, Intervention, Evaluation, and Termination Stages. The practitioner hopes that going through these stages can help the process of solving the child’s problem.